Regenerasi Tanaman dari Kalus Tebu yang Diiradiasi Sinar Gamma pada Medium dengan PEG 6000 - Purwito, Agus; Ravenska, Nidya; Maharijaya, dan Awang (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTSugarcane cultivars tolerant to drought stress are needed for specific location. In vitro selection can be used to obtain plants tolerant to drought stress through regeneration of callus in the culture medium. The purpose of this study was to obtain regenerants from irradiated callus on the stress medium. The experimental design was a completely randomized design with two factors. The first factor was the regeneration medium (RG) added with PEG 6000, i.e., 0%, 5%, 10% and 15%, while the second factor was the dose of gamma ray irradiation i.e. 0 krad, 5 and 10 krad, and 15 krad. There were 12 treatments, each treatment was repeated 18 times and each repetition was a culture bottles planted with three clums of callus 10 mm diameter. RG medium was the MS medium added with 0.5 mg L-1 BAP, Kinetin 0.1 mg L-1 and IBA 1.0 mg L-1. The higher the concentration of PEG, the less regenerants were produced. Regenerants could be generated from the selection medium PEG up to 15%. Several shoots still produced from callus irradiated with 10 krad. Selection medium with PEG up to 10% decreased the precentage of albino regenerants. The gamma ray irradiation dose and the concentration of PEG significanly affected the number of  roots produced.Keywords: drought tolerant, in vitro, polyethylene glycol, plantlets, albino